Tolerance: Understanding and Teaching - Sprindžiūnas, Andrius (Acta Paedagogica Vilnensia, 1998)
There is a lack of tolerance in post-Soviet Lithuania and it manifest itself in various spheres of social life. Tolerance is a humanistic value, closely related to the democracy, respect of the human person, human rights and freedom. The analysis of tolerance understanding of outstanding Lithuanian philosophers and pedagogues helps to reveal main elements and the structure of this important value. The urge to teach tolerance in secondary schools is evident. Some factors, important in teaching tolerance, like family, school life, and various youth organisations are discussed.